Comparative efficacy of antibody-drug conjugates and chemotherapy for malignant tumors: a systematic review and meta-analysis - Gao, Xin; Tao, Linghui; Hao, Wen; Wu, Xiaqiu; Zhu, Feiye; Lv, Shengxia; Zhang, Yongsheng (Frontiers in Oncology, 2026)
BackgroundDespite advancements in cancer treatment, malignant tumors remain a significant global health challenge. Drawbacks of chemotherapy, such as drug resistance and strong side effects, have prompted the exploration of antibody-drug conjugates (ADCs), which combine targeting capabilities with potent cytotoxins to enhance therapeutic efficacy.MethodsWe searched PubMed, Cochrane, and EMBASE library databases up to June 8, 2025, for eligible randomized controlled trials (RCTs) and extracted relevant data. The primary outcome measures were overall survival (OS) and progression-free survival (PFS), with subgroup analysis and sensitivity analysis conducted to assess the heterogeneity of statistical results.ResultsA total of thirteen RCTs involving 5,927 patients were included. The results indicated that ADCs offered superior OS (HR = 0.67, 95%CI: 0.55-0.81) and PFS (HR = 0.76; 95% CI: 0.66-0.86) compared to chemotherapy drugs. The any adverse event (96.8% vs. 93.6%), grade 3–5 adverse event (51.7% vs. 51.8%) and serious adverse event (25.3% vs. 22.4%) caused to patients were generally similar between ADCs and chemotherapy.ConclusionOur meta-analysis demonstrates that compared to chemotherapy drugs, ADC drugs can prolong both OS and PFS in cancer patients, with no significant difference in adverse reactions.Systematic Review Registrationhttp://www.crd.york.ac.uk/PROSPERO, identifier CRD42024592020.